Corporate green pledges - Michael Bauer; Daniel Huber; Eric Offner; Marlene Renkel; Ole Wilms (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
We identify corporate commitments for reductions of greenhouse gas emissions - green pledges - from news articles using a large language model. About 8% of publicly traded U.S. companies have made green pledges, and these companies tend to be larger and browner than those without pledges. Announcements of green pledges significantly and persistently raise stock prices, consistent with reductions in the carbon premium. Firms that make green pledges subsequently reduce their CO2 emissions. Our evidence suggests that green pledges are credible, have material new information for investors, and can reduce perceived transition risk.
Keywords: G14; G32; Q54; Q56; 330; climate finance; decarbonization commitments; text classification; event study; transition risk; carbon premium